Traumatic arteriovenous fistulas lower limbs for gunshot wounds - López Chapuis, Daniel; Siécola, Osvaldo; Olivera, Daniel (Cirugía del Uruguay, 1994)
Traumatic arterio-venous fistulas are a rare type of vascular lesion, of frequent late diagnosis. lts early recognition is based on a careful search far signs of vascular lesion. The value of arteriography is pointed out. As regards 5 cases of trauma tic arterio-venous fistulas of the lower limbs caused by fire-arm injuries, the importance of early treatment is emphasized, with repair of arterial and venous lesion.